Xenobiotics and inflammation - Schook, Lawrence B.; Laskin, Debra L. (Academic Press, 1994)
The effect of xenobiotics on general host resistance and on specific immune functions has recently become the focus of much research. Xenobiotics and Inflammation synthesizes current information on how chemicals (xenobiotics) can modulate the immune system, focusing on the process of inflammation. It provides a much needed, single-source reference for researchers investigating the mechanisms responsibIe for altered host resistance following exposure to xenobiotics.